The environmental impact of polycyclic aromatic hydrocarbons in the sediment river - Nurul Ain, Zainodin (2017)
Polycyclic Aromatic Hydrocarbons (PAHs) are ubiquitous in the environment and amongst greatest concern due to their toxicity and mutagenicity. As the occurrences of PAHs in Malaysia have been reported, thus this study was conducted to further assess their environmental impact in river sediments by determination of PAHs behavior and factors that govern it. The research started with the investigation of the sorption capacity or affinity of these PAHs in sediments and the relationship between sorption and their octanol-water partition coefficient (Kow). The octanol-water partition coefficient (Kow) was a good predictor of sorption among pollutant as the results show that the solid-water partition coefficient (Koc) increased as the octanol-water partition coefficient (Kow) increased. The sorption data was plotted to graphs Linear, Freundlich and Langmuir isotherm model and the linear regression coefficient (R2) obtained for Freundlich isotherm was the highest (>0.98) among these three models. Thus, the sorption behavior of PAHs in river sediments was physisorption as it obeyed the Freundlich isotherm model. A significant effect on PAHs behavioral was observed in sediments caused by changes of salinity, pH and temperature which was indicated by the sorption capacity coefficient (Kf) obtained from batch sorption equilibrium experiments. The sorption capacity coefficient (Kf) increased as the salinity increased but vice versa as the pH and temperature was increased. The pseudo-first order, pseudosecond order, Elovichs’ equation and fractional power model graphs was plotted and pseudo-second order represents the adsorption kinetic mechanism since it has the highest linear regression coefficient (R2>0.99). Pseudo-second order confirmed that presence of pores in the sediments system was the limiting factor to the adsorption rate mechanism. Besides that, three different method of solid phase extraction were applied to pre-concentrate the samples and the method from Supelco show the highest percentage of recovery (73.53% to 88.29%) compared to other method from previous literature. Finally, the results of this study also indicated a considerable difference between experimental values and values generated by the computational model, Estimation Program Interface (EPISUITE). Thus, this study strongly shows that although the computational model was indicative, it does not accurately assess the environmental impact of pollutant. The experiments need to be conducted to obtain the real partitioning of PAHs in environment.